2016
DOI: 10.1242/bio.017319
|View full text |Cite
|
Sign up to set email alerts
|

Physiological profiles associated with ceasing growth of unfertilized eggs produced by unmated queens in the subterranean termite Reticulitermes chinensis

Abstract: In Reticulitermes chinensis, a close relative of R. speratus with asexual queen succession, unfertilized eggs can be produced but do not hatch as larvae. To explain this phenomenon, we analyzed the physiological differences between unfertilized eggs/unmated queens and fertilized eggs/mated queens. Fertilized eggs had significantly lower quantities of five amino acids (Cys, Met, Ile, Leu and Tyr), Ca, protein and cholesterol during development. The higher levels of four trace elements (Na, K, Zn and Fe) in fert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Hence, a number of micropyles were found on eggs laid by female-female colonies of both species in this study, which concurred with previous reports, in which micropyles were present on the parthenogenetic eggs of the termite R. speratus during the early colony stage [40,41]. Contrary to previous research, no micropyles were found on the unfertilized eggs of R. chinensis [41]. However, we found micropyles on the fertilized and unfertilized eggs of both R. flaviceps and R. aculabialis (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, a number of micropyles were found on eggs laid by female-female colonies of both species in this study, which concurred with previous reports, in which micropyles were present on the parthenogenetic eggs of the termite R. speratus during the early colony stage [40,41]. Contrary to previous research, no micropyles were found on the unfertilized eggs of R. chinensis [41]. However, we found micropyles on the fertilized and unfertilized eggs of both R. flaviceps and R. aculabialis (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…While the cleavage rate of newly produced eggs might have been higher due to the mitosis of the maternal mRNA protein, with the degradation of maternal mRNA, the rate of cleavage slowed and the egg initiated the nucleus genome to encode for new protein synthesis [10,41]. The egg development of R. flaviceps ceased in the blastoderm formation after approximately 8-10 days postoviposition.…”
Section: Discussionmentioning
confidence: 99%
“…The typical examples were observed in many social insect species (e.g. ant or termite) that the micropyle structure disappeared on eggs produced by virgin workers 11,12 . Here, for H. axyridis , almost 17 micropyles were still presented on eggs from virgin female.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the number of micropyles also showed to be influenced by the experience of copulation (or called fertilization). For example, virgin female workers of the ant, Gnamptogenys menadensis (Hymenoptera: Formicidae) and virgin queen of the subterranean termite, Reticulitermes chinensis (Isoptera: Rhinotermitidae) can only lay small number of eggs lacking micropyle; while those females following mating produced a mass number of eggs presenting micropyles 11,12 . Queens of the termite, Reticulitermes speratus (Isoptera; Rhinotermitidae), in particular, could close the gate of micropyle to switch from sexual to asexual reproduction when the kings were presented 13 .…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference in the number of eggs produced parthenogenetically and the eggs sexually in R. chinensis, R. labralis and R. speratus. There was a significant difference in the number of eggs in the two females without the parthenogenetic ability (Xing unpublished data (Li et al, 2016a).…”
Section: /15mentioning
confidence: 99%